Advocacy Process for Rural and Urban Land and Building Tax Policies in Kuripan Village, Purwodadi District - Faiq Najib Hasan; Retno Sunu Astuti; R. Slamet Santoso (Eduvest - Journal of Universal Studies, 2024)
Regulations regarding Land and Building Tax (PBB) have been regulated in Law Number 12 of 1985 which was later amended by Law Number 12 of 1994 concerning Land and Building Tax. PBB-P2 is a tax imposed on land and/or buildings owned, controlled, or utilized by individuals or entities, except for the plantation, forestry, mining, and public facilities sectors. Awareness of paying taxes is considered a form of commitment from the community as taxpayers. This study analyzes the PBB-P2 policy advocacy process in Grobogan Regency and analyzes its supporting and inhibiting factors, with a special focus on Kuripan Village. This study uses a qualitative descriptive method with an inductive approach, through direct observation, in-depth interviews and analysis of supporting documents. Interviews were conducted with related parties such as the Purwodadi Sub-district Head, the Head of Kuripan Village, PBB-P2 Collecting Officers, and Taxpayers. The results of the study show that although this policy has yielded positive results, there are still challenges such as lack of communication and socialization, delays in the distribution of SPPT and low level of public understanding. Innovations such as payments by mobile banking, PBB-P2 Payment Posts, and PBB-P2 intensification have been implemented, but they are still not optimal. Intensive communication with stakeholders, continuous socialization, and policy support can improve the optimization of PBB-P2 and contribute to increasing the Realization of PBB-P2 Revenue in Kuripan Village and contribute to the Regional Original Revenue (PAD) in Grobogan Regency.